БУҒЛАНИШ ВА КОНДЕНСАЦИЯ МАВЗУСИНИ ЎҚИТИШДА ЭКОЛОГИК ТУШУНЧАЛАРНИ ШАКЛЛАНТИРИШ - Очилов, Ш.Б. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of ecological upbringing based on the connections among the natural sciences in teaching the topic «Evaporation and condensation».